Practicality of Student-Centered Assessment/Learning using Mathematics Modeling Process Worksheets to Improve the Quality of Education - Riyanto, Bambang (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2024)
It is necessary to consider reforms to improve the quality of education through assessment/learning. The problem formulation of this research is how to design student-centered assessment/learning using practical mathematical modeling process worksheets to improve the quality of education? This research uses a development research approach developed by Akker, Gravemeijer, McKenney and Nieveen. This development research consists of 3 steps, namely analysis, design and evaluation. In the analysis step, student analysis, curriculum, mathematical modeling and real world problems are implemented. Second step, design and product. In the final step, researchers used a formative evaluation design consisting of self-evaluation, one-to-one, expert review, small group, and field test. Data were analyzed using descriptive analysis methods: (1) walk through, analysis based on solutions and student comments in small groups to obtain student-centered assessment/learning using mathematical modeling process worksheets using the best practical transportation context to improve the quality of education; (2) analyzing the results of the review of small group results. Based on the results of the small group worksheet, the mathematical modeling process is practical for improving the quality of education. Students commented that this mathematical modeling process worksheet was interesting, confusing but challenging and had never been found in their classrooms. Students can solve problems on process worksheets even though the mathematization process has not yet appeared, because students only solve them using informal methods. So, this is a golden opportunity to implement in order to improve the quality of education through assessment/learning. So, a practical mathematical modeling process worksheet is obtained to implement student-centered assessment/learning in order to improve the quality of education.